(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
Globalization has been understood as a form of global homogenization, based on this principle, social networks are playing a leading role in that trend. Every day, social networks become more relevant as matrices of opinions are built around a reality that, in view of each person on their respective social platforms, can vary in interpretation or meaning. The interference with internal matters has also been homogenized more directly, since, from social networks, anyone can give an opinion on realities of which they are not participating, beyond what they see on virtual platforms. This reflection is reflexive, an essay that pays for this discussion based on bibliographic records and argumentation.